Reductions in Parental Use of Corporal Punishment on Pre-School Children Following Participation in the Moms' Empowerment Program. Issue 8 (April 2019) - Grogan-Kaylor, Andrew; Galano, Maria M.; Howell, Kathryn H.; Miller-Graff, Laura; Graham-Bermann, Sandra A.
Corporal punishment is a widely used and widely endorsed form of parental discipline. Inter-partner violence places enormous stress upon women. The rate of corporal punishment is higher in homes where other types of domestic violence are also occurring. This study compares two groups: those who participated in an intervention for women exposed to intimate partner violence (The Moms' Empowerment Program [MEP]) and those in a comparison group. Using standardized measures, women in both groups were assessed at baseline and at the end of the program, 5 weeks later. The 113 mothers who participated in the MEP program had significantly improved their parenting, such that they had less use of physical punishment post-intervention. Findings suggest that a relatively brief community-based intervention program can reduce the use of parental physical punishment even in disadvantaged populations coping with stressful circumstances.